Revitalizing Educational Leadership: A Comprehensive Literature Review of Transformational Leadership in Indonesia Academic Settings - Hardianto Hardianto; Hidayat Hidayat; Ayu Wulandari; Sulastri Sulastri; Nofriser Nofriser (AL-ISHLAH: Jurnal Pendidikan, 2024)
This research was motivated by the limited research on the transformational leadership style of school principals. Transformational leadership is mostly researched on company leaders. This research aims to describe previously published research on transformational leadership of school principals. This research uses a literature review method, with the main source being articles that have been published in the journals Sinta 1 and Sinta 2. Search for articles using the keywords transformational leadership and “kepemimpinan transformasional”. Data analysis was carried out deductively, inductively, interpretatively, comparatively and historically. The research results show that thirteen variables are influenced by the principal's transformational leadership. Three variables moderate the influence of transformational leadership on other variables. A transformational school principal can be a source of inspiration for teachers and education staff.